The conserved AU dinucleotide at the 5′ end of nascent U1 snRNA is optimized for the interaction with nuclear cap-binding-complex. Issue 16 (13th July 2017) - Yeh, Chung-Shu; Chang, Shang-Lin; Chen, Jui-Hui; Wang, Hsuan-Kai; Chou, Yue-Chang; Wang, Chun-Hsiung; Huang, Shih-Hsin; Larson, Amy; Pleiss, Jeffrey A; Chang, Wei-Hau; Chang, Tien-Hsien
Abstract: Splicing is initiated by a productive interaction between the pre-mRNA and the U1 snRNP, in which a short RNA duplex is established between the 5′ splice site of a pre-mRNA and the 5′ end of the U1 snRNA. A long-standing puzzle has been why the AU dincucleotide at the 5′-end of the U1 snRNA is highly conserved, despite the absence of an apparent role in the formation of the duplex. To explore this conundrum, we varied this AU dinucleotide into all possible permutations and analyzed the resulting molecular consequences. This led to the unexpected findings that the AU dinucleotide dictates the optimal binding of cap-binding complex (CBC) to the 5′ end of the nascent U1 snRNA, which ultimately influences the utilization of U1 snRNP in splicing. Our data also provide a structural interpretation as to why the AU dinucleotide is conserved during evolution.